2008
DOI: 10.1080/10401330802384599
|View full text |Cite
|
Sign up to set email alerts
|

Reading Habits and Attitude Toward Medical Humanities of Basic Science Students in a Medical College in Western Nepal

Abstract: Students read widely beyond their course. The possibility of introducing medical humanities in the curriculum should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
1
9
0
2
Order By: Relevance
“…Their second choice of British authors, protagonists and settings also shows their interest in and preference for the English-speaking world over their own world because Arab authors, protagonists and settings came in at little over one tenth of their reading choices. Referring to a similar dilemma in their own findings in Nepal, Shankar et al (2008) suggest two factors which may result in respondents' low interest in reading South Asian authors: "the higher socioeconomic class of the respondents and education in English medium schools" (p.312), both of which could also be key factors in the reading choices of the Emirati students in this study.…”
Section: What's Geography Got To Do With It?supporting
confidence: 63%
See 3 more Smart Citations
“…Their second choice of British authors, protagonists and settings also shows their interest in and preference for the English-speaking world over their own world because Arab authors, protagonists and settings came in at little over one tenth of their reading choices. Referring to a similar dilemma in their own findings in Nepal, Shankar et al (2008) suggest two factors which may result in respondents' low interest in reading South Asian authors: "the higher socioeconomic class of the respondents and education in English medium schools" (p.312), both of which could also be key factors in the reading choices of the Emirati students in this study.…”
Section: What's Geography Got To Do With It?supporting
confidence: 63%
“…As more academic libraries open recreational reading sections to promote leisure reading (Hurst, Marsh, Brown, & Forbes, 2017), findings from investigations such as the one reported here, offer evidence of students' choices which helps librarians and educators make informed decisions when selecting and recommending books (Hodgson and Thompson, 2000). There is evidence that having such books available encourages students to read them (Shankar, Dubey, Mishra, & Upadhyay, 2008).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…The most recent study on MedLine on the arts and leisure pursuits of medical students is almost 50 years old,33 two further studies examine the reading habits of medical students (a typical manifestation of the heavy emphasis on literature in much of the medical humanities),34 35 and an unpublished doctoral study in the UK on the determinants of ethical attitudes among medical students found marked heterogeneity and high levels of engagement in culture 36…”
Section: Existing Programmesmentioning
confidence: 99%